The Symbiotic Future of Care: AI Patient Monitoring vs. Nurse Monitoring - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The healthcare landscape is undergoing a profound transformation, driven by the convergence of Artificial Intelligence AI and traditional nursing care. The d...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care